2006
DOI: 10.1021/bi052660s
|View full text |Cite
|
Sign up to set email alerts
|

Structures of Staphylococcus aureus Cell-Wall Complexes with Vancomycin, Eremomycin, and Chloroeremomycin Derivatives by 13C{19F} and 15N{19F} Rotational-Echo Double Resonance

Abstract: Solid-state NMR has been used to examine isolated cell walls and intact whole cells of Staphylococcus aureus complexed to 5 different vancomycin, eremomycin, and chloroeremomycin derivatives. The cell walls and whole cells were specifically labeled with D-[1-13 C]alanine, or a combination of [1-13 C]glycine and [ε-15 N]lysine. Each of the bound glycopeptides had a 19 F-labeled substituent at either its C-terminus or disaccharide position. The 13 C{ 19 F} rotational-echo doubleresonance (REDOR) dephasing for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
131
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(138 citation statements)
references
References 47 publications
4
131
0
1
Order By: Relevance
“…Here, we provide evidence at the molecular level that these structural modifications enable oritavancin, in contrast to vancomycin, to bind to further target sites of the lipid II peptidoglycan precursor other than the D-Ala-D-Ala terminus. With use of solidstate nuclear magnetic resonance (NMR) and rotational-echo double resonance (REDOR), a model for the oritavancin-PG complex has been proposed in which the crossbridge is bound in a cleft between the epi-vancosamine residue and the core of the oritavancin molecule (36,39,40). We now provide biochemical evidence that the crossbridge and the D-iso-glutamine in position 2 of the lipid II stem peptide represent crucial binding sites for oritavancin.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Here, we provide evidence at the molecular level that these structural modifications enable oritavancin, in contrast to vancomycin, to bind to further target sites of the lipid II peptidoglycan precursor other than the D-Ala-D-Ala terminus. With use of solidstate nuclear magnetic resonance (NMR) and rotational-echo double resonance (REDOR), a model for the oritavancin-PG complex has been proposed in which the crossbridge is bound in a cleft between the epi-vancosamine residue and the core of the oritavancin molecule (36,39,40). We now provide biochemical evidence that the crossbridge and the D-iso-glutamine in position 2 of the lipid II stem peptide represent crucial binding sites for oritavancin.…”
Section: Discussionmentioning
confidence: 87%
“…In VRSA, the terminal D-Ala residue is exchanged to D-Lac, and it has been proposed that oritavancin compensates for the resulting loss of one critical hydrogen bond to this target through the interaction with additional binding sites on the lipid II molecule, i.e., the crossbridge (36,39). However, vanA-type vancomycinresistant S. aureus strains are characterized by a complete lack of or an incomplete chain length of the pentaglycine crossbridge (41), suggesting that in these strains yet another binding site on the lipid II molecule contributes to the high-affinity binding.…”
Section: Oritavancin Blocks Individual Cell Wall Biosynthesis Reactiomentioning
confidence: 99%
See 1 more Smart Citation
“…Within our analysis, we detected signals corresponding to cell wall polysaccharides derived from N-acetyl termini (2.02÷2.33/4.10÷4.33 ppm) (27). This is in accordance with our previous results (28) which demonstrated that the PA cell wall contains peptidoglycans, and is a thick rigid layer composed of an overlapping lattice of the sugars, N-acetyl glucosamine (NAG) and N-acetyl muramic acid (NAM), cross-linked by amino acid bridges (2003)(2004)(2005)(2006), The Microbical World http://www.microbiologytext.com).…”
Section: Discussionmentioning
confidence: 99%
“…Since oritavancin readily forms dimers in solution and binds to membrane vesicles (8), drug dimerization and membrane anchoring mediated by the hydrophobic side chain of oritavancin are thought to increase its binding to the D-Ala-D-Lac-terminated PG stem structure to overcome the vancomycin resistance in VRE (9). However, in situ characterizations of oritavancin (10) and oritavancin-like glycopeptide (4,11,12) binding sites in intact whole cells of S. aureus by solid-state nuclear magnetic resonance (NMR) have shown that lipoglycopeptides do not bind to the cell wall as dimers or partition to the bacterial membrane. The only instance of oritavancin's hydrophobic side chain being found inserted into the lipid bilayer was when it was complexed to an isolated protoplast membrane of S. aureus.…”
mentioning
confidence: 99%